Penerapan Sanksi Perdata terhadap Korporasi dalam Sengketa Lingkungan Hidup - Eko Nurisman; Dwi Meilya Sandy (Journal of Judicial Review, 2016)
The rise of industry by utilizing natural resources has risks the impact on environmental pollution. This research will answer two legal issue, first concerning the application of civil penalties on corporations that pollute the environment with wastewater in environmental disputes; sedondy, regarding accountability corporations in environmental disputes. The special purpose of this studyis to analyze the judicial verdict and spesificly remedy after environmental pollution. This is a normative legal research. The source data is secondary data which collect from the literature (library research). After all the data has been collected, then processed and analyzed by descriptive-qualitative approach. The result drawn from the study conclude that the application of civil penalties suffered by the victim is materially own right but has not been effective because the perpetrators of environmental pollution shall perform certain actions whose nature is to improve the ecosystem and environmental sustainability life so that it can be used accordingly.